Rainwater harvesting system Laman PKNS, Shah Alam Selangor / Nur A’thifah Aziz - Aziz, Nur A’thifah (Universiti Teknologi Mara, Perak, 2017)
Laman PKNS building is considered as green building since this building using a lot of green technology methods to make it more efficiency. In this chapter also will be explain in detail about the building and organization chart. Also provided some other information about this building such as view from any angle of the building, facilities and adjacent of building. For surrounding area, Laman PKNS building is construct at commercial area in Shah Alam.